Systematic Literature Review: Kemampuan Pemodelan Matematika Siswa SMP - Syifa Afidah Nurul Arifin (Griya Journal of Mathematics Education and Application, 2025)
This study aims to examine the mathematical modeling skills of junior high school (SMP) students through the Systematic Literature Review (SLR) approach. By using the PRISMA guidelines and examining 13 selected articles published between 2014 and 2023. The findings show that the majority of junior high school students have high mathematical modeling skills, with 48% of articles reporting strong performance. However, some studies also show moderate to low ability. Mathematical modeling has an important role in bridging abstract mathematical concepts with real situations, so that it can improve students' problem-solving skills. A variety of factors influence these skills, including learning styles, teaching approaches, and the use of real-world contexts and technology in the learning process. The data also shows that the provinces of Sumatra and Java are the most active regions in publishing research related to this topic. To improve students' modeling skills, this study recommends the use of problem-based learning approaches, the use of educational technology, and improved teacher training in designing contextual and interactive learning. This study emphasizes the importance of developing mathematical modeling skills at the junior high school level as a strategy to improve the quality of mathematics education in Indonesia.